Redeem all how digital life is changing evangelical culture - Laughlin, Corrina, 1984- (University of California Press, 2022)
"Redeem All examines the surprising intersection of American evangelicalism and tech innovation. Corrina Laughlin looks at the evangelical Christians who are invested in imagining, using, hacking, adapting, and sometimes innovating new media technologies for religious purposes. She finds that entrepreneurs, pastors, missionaries, and social media celebrities interpret the promises born in Silicon Valley through the frameworks of evangelical culture and believe that digital media can help them (to paraphrase Steve Jobs) put their own dent in the universe. Laughlin introduces readers to "startup churches" hoping to reach a global population, entrepreneurs coding for a deeper purpose, digital missionaries networking with mobile phones, and Christian influencers and podcasters seeking new forms of community engagement. Ultimately, Redeem All reveals how evangelicalism has changed as it eagerly adopts the norms of the digital age"--